Aproximações entre a Psicoterapia e a Ioga - Campagnone, Larissa Zanelato (2013)
This study aimed to understand the connection between yoga and psychotherapy. This work wants to comprehend the relationship between these two areas, there are few studies addressing this approach. It was organized in two stages: ( a) theoretical and empirical literature review and ( b ) qualitative research , resulting in analysis of great authors works of psychology, including , Jung (1996 ) and Lowen (1977 .) This methodology was chosen because the literature review opens the possibility of studying to understand what other authors present on the subject matter and explain theoretically the results of the analysis. Moreover, qualitative research enables understanding subjective and affective aspects of each participant. Participated in the survey, six therapists yoga practitioners. Questionnaires were open, trying to understand what they perceived approaches between these two areas. From the questionnaires, it was found that all participants believe that: yoga teachers would benefit greatly if they learned some techniques of psychotherapy to thus be more efficient in accommodating their students when they come in contact with some feeling in their yoga classes. All participants reported changes in their behavior after beginning to practice yoga, thus showing that this philosophy has helped them feel: more tolerant, less anxious, healthy and in balance. Through this study, it was realized that yoga techniques such as meditation, physical postures, breathing and some can be a tool used by psychotherapists. Suggest to discussions in forums about the study of professional associations on psychotherapeutic practice. Supported by CNPq